Clinical spectrum and prognostic impact of precipitating factors in hepatic encephalopathy among patients with liver cirrhosis: a cross-sectional observational study - Khan, Yafas Nazir; Mansi; Louis, Rolanda Saint; Ashraf, Shehla; Paidi, Purna Chand (International Journal of Research in Medical Sciences, 2026)
Background: Hepatic encephalopathy (HE) is a serious neuropsychiatric complication of liver cirrhosis associated with significant morbidity and mortality. Early identification of precipitating factors is essential for timely management and improved clinical outcomes. Methods: A hospital-based cross-sectional observational study was conducted among 110 patients with cirrhosis of liver presenting with hepatic encephalopathy at a tertiary care teaching hospital. Clinical history, physical examination, laboratory investigations, and radiological evaluation were performed to identify precipitating factors. Hepatic encephalopathy was graded using the West Haven classification, while liver disease severity was assessed using the Child-Pugh score. PHES and Stroop tests were performed in eligible patients. Clinical outcomes, including recovery and mortality, were analyzed. Results: Most patients were middle-aged males with alcohol-related cirrhosis. Grade II hepatic encephalopathy and Child-Pugh class C were the most common presentations. Asterixis, icterus, and ascites were frequent clinical findings. At least one precipitating factor was identified in most patients, with constipation, infections, upper gastrointestinal bleeding, electrolyte imbalance, vomiting/diarrhoea, and acute kidney injury being the commonest. Neuropsychometric abnormalities were frequently detected. Higher grades of hepatic encephalopathy and advanced Child-Pugh class were significantly associated with poorer outcomes and increased mortality. Conclusions: Hepatic encephalopathy is commonly precipitated by identifiable and potentially reversible factors. Early recognition and prompt correction of these factors, together with timely assessment of disease severity, are essential to improve prognosis and reduce morbidity and mortality in patients with liver cirrhosis.